2022
DOI: 10.1080/21655979.2022.2048991
|View full text |Cite
|
Sign up to set email alerts
|

UBE2B promotes ovarian cancer growth via promoting RAD18 mediated ZMYM2 monoubiquitination and stabilization

Abstract: Ubiquitin-conjugating enzyme E2 B (UBE2B) can form a heterodimer with ubiquitin E3 ligase RAD18. In this study, we aimed to explore new substrates of the UBE2B/RAD18 complex and their regulatory effects in ovarian cancer. Protein physical interactions were predicted using GeneMANIA. Serial sections of commercial ovarian cancer tissue arrays were used to check the protein expression of UBE2B, RAD18, and ZMYM2. Immunofluorescence staining and co-immunoprecipitation assays were performed to check their location a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Emerging functions of ubiquitination modification in CSCs, cellular senescence, and immune infiltration have been affirmed, including roles in tumor metabolism regulation, tumor immune microenvironment modulation, cancer stem cell stemness maintenance, and cellular senescence induction [ 19 ]. Schimmer et al proved that inhibiting the E1-activating enzyme UBA1 reduced leukemia burden and specifically targeted leukemia stem cells [ 20 ]; Ma et al demonstrated that the E2-conjugating enzyme UBE2B promoted ovarian cancer growth [ 21 ]; Wang et al discovered that deleting the E3 ligases TRIM29 inhibited PDAC’s cancer stem cell-like properties by accelerating ISG15 degradation [ 22 ]; Lee et al revealed that USP1-mediated protein stabilisation promoted GSC maintenance and treatment resistance [ 23 ]. Besides, targeting E3 ligase Skp2 attenuates aerobic glycolysis and induces cellular senescence in cancer cells, thereby reducing CSC populations and their function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging functions of ubiquitination modification in CSCs, cellular senescence, and immune infiltration have been affirmed, including roles in tumor metabolism regulation, tumor immune microenvironment modulation, cancer stem cell stemness maintenance, and cellular senescence induction [ 19 ]. Schimmer et al proved that inhibiting the E1-activating enzyme UBA1 reduced leukemia burden and specifically targeted leukemia stem cells [ 20 ]; Ma et al demonstrated that the E2-conjugating enzyme UBE2B promoted ovarian cancer growth [ 21 ]; Wang et al discovered that deleting the E3 ligases TRIM29 inhibited PDAC’s cancer stem cell-like properties by accelerating ISG15 degradation [ 22 ]; Lee et al revealed that USP1-mediated protein stabilisation promoted GSC maintenance and treatment resistance [ 23 ]. Besides, targeting E3 ligase Skp2 attenuates aerobic glycolysis and induces cellular senescence in cancer cells, thereby reducing CSC populations and their function [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has verified that E2s show dysregulation in various cancer types, as they are linked to tumor-promoting processes and self-renewal abilities such as dysregulation in DNA repair, cell cycle, apoptosis and oncogenic signalling (10,(17)(18)(19)(20)(21)(22). The dysfunctional status of E2 members is considered a potential biomarker for diagnosis, prognosis and therapy in patients with various cancer types (22)(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Ube2tmentioning
confidence: 99%
“…Six of them encode methyltransferases (Setd4, Setdb1, Smyd3, Suv39h1, Suv420h1, and Whsc1), two encode demethylases (Kdm1a and Kdm5b), three encode acetyltransferases (Esco2, Hat1, and Myst3), one encodes histone deacetylase (Hdac5) [25,26], and one encodes DNA methylase (Dnmt1) [27]. Two genes encoding proteins involved in the ubiquitination process were also affected (Ube2b and Usp22) [28,29].…”
Section: Agnps Treatment Affects the Expression Of Chromatin-modifyin...mentioning
confidence: 99%